2021
DOI: 10.1002/psp.2431
|View full text |Cite
|
Sign up to set email alerts
|

Feeling at home across time and place: A study of Ecuadorians in three European cities

Abstract: International migration creates significant dilemmas for people to feel at home or not and a meaningful field to investigate this emotional experience. Using a cross‐country survey of Ecuadorians in Madrid, Milan and London (n = 1093), we explore how spatial, relational, infrastructural and emotional variables influence the sense of feeling at home in a place. We link these aspects to length of residence and the location's ‘connectedness’ to Ecuador. Immigrants' sense of feeling at home increases over time, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Moreover, MOs importantly contribute to the formation of group identities and relationships of trust (Ibid.). In this way, they also engage in activities related to what Boccagni and Vargas-Silva (2021) refer to as "homemaking". Finally, recent studies have shown that many MOs increasingly offer more formalized social services of their own (Halm et al 2020).…”
Section: Migrant Organizations and Their Functionsmentioning
confidence: 99%
“…Moreover, MOs importantly contribute to the formation of group identities and relationships of trust (Ibid.). In this way, they also engage in activities related to what Boccagni and Vargas-Silva (2021) refer to as "homemaking". Finally, recent studies have shown that many MOs increasingly offer more formalized social services of their own (Halm et al 2020).…”
Section: Migrant Organizations and Their Functionsmentioning
confidence: 99%
“…However, home as 'reproduction' and 'making anew' may well diverge over time. Long-settled migrants tend to connect a sense of home to better life conditions where they are staying, more than to the retention of their past lifestyles (Boccagni and Vargas-Silva 2021). Along this process of 'familiarization' and 'naturalization', objects can keep playing a significant role in multiple respects (Banerjee 2016).…”
Section: Conceptualizing Homemaking and The Reproduction Of Homementioning
confidence: 99%
“…As the latter asks if he is considering adding the Union Jack, Marlon replies: 'I have not thought about this yet'. His answer does not only suggest that feeling at home in a new country takes time (Boccagni and Vargas-Silva 2021). It also illustrates the value of objects themselves in creating a home environment in a country that is not yet experienced as home and how objects help migrants to connect multiple places and multiple experiences of home.…”
Section: Embodying Migrant Collective Background and Identitymentioning
confidence: 99%
“…Importantly, though, the distinction between affective and physical home may blur over time (Boccagni & Vargas-Silva 2021). Sharing domestic spaces and life course positions with one's peers opens up to new forms of commonality and conviviality (Holton 2016).…”
Section: Home Culturesmentioning
confidence: 99%
“…They are reluctant to associate feelings of being at home with either the parental home(land) or their present accommodation. The constitutive provisionality of their stay pushes them to ponder thoroughly where their stable home, or at least a place to feel home (Boccagni & Vargas-Silva 2021), may be afterwards: I'm not even sure if I will have a home [laughs]… seriously, right now I don't have one because in less than two months I'm going away, so I just can't. I mean, 5 months ago I would say this place, but now… I would say I don't have a home, but I have a family house.…”
Section: Home As Open-endednessmentioning
confidence: 99%